„Berlin mitten im Herzen getroffen“ - Diskursive Opferkonstruktionen in parlamentarischen Debattenreden über Terrorismus in Deutschland - Ylä-Mattila, Anna-Maija (Linguistik Online, 2023)
Through their discursive actions, parliamentarians have an impact on the public perception of societal issues. Drawing on the Discourse-Historical Approach of Critical Discourse Studies this paper strives to illuminate how persons, objects, or abstract things are discursively constructed as victims. The debate speeches relate to two cases of terrorism: The National Socialist Underground (NSU) and the ISIS attack at Breitscheidplatz in Berlin. After first identifying the types of victims in the data, the study then conducts a detailed analysis of the discursive resources that are used in the construction process. Furthermore, the victim constructions are interrogated in terms of their strategic political aims. Apart from linguistic means, different context levels play a crucial role in the construction. The examined victim constructions aimed for example at the sense of unity (Wir-Gefühl) and presenting the own party in a certain light. The study shows how the discursive construction of victims contributes to the construction of reality for the public and how they serve different kinds of strategic and political aims.